2019
DOI: 10.1111/jan.14018
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a WeChat‐based life review programme for cancer patients: A quasi‐experimental study

Abstract: Aim To evaluate the feasibility and effects of the WeChat‐based life review programme on anxiety, depression, self‐transcendence, meaning in life and hope among cancer patients. Background Life review is effective in improving the psychospiritual well‐being of palliative patients. However, traditional life review programmes are limitedly applied in clinical practice. Design A non‐concurrent controlled quasi‐experimental design. Methods Ninety‐two cancer patients were recruited from April 2017 – February 2018, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 27 publications
2
54
0
Order By: Relevance
“…Hu et al [23] revealed that transitional care delivered by WeChat could decrease depression and anxiety in discharged patients with AS. Similarly, WeChat-based interventions also have significant effects on reducing depression in people living with HIV [34], cancer patients [21], and pregnant women [35]. The education delivered by social media platform, WeChat, can optimize communication between patients and health care professionals and teach patients psychological management strategies [18,23], which might improve psychological outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hu et al [23] revealed that transitional care delivered by WeChat could decrease depression and anxiety in discharged patients with AS. Similarly, WeChat-based interventions also have significant effects on reducing depression in people living with HIV [34], cancer patients [21], and pregnant women [35]. The education delivered by social media platform, WeChat, can optimize communication between patients and health care professionals and teach patients psychological management strategies [18,23], which might improve psychological outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Zhang et al revealed that individualized health education through WeChat can play a central role in health education efforts in China because WeChat is well-integrated into society [18]. In recent years, some studies have found that interventions delivered by WeChat can improve health behaviors and health outcomes in patients with other chronic diseases [19][20][21][22]. Hu et al [23] explored the transitional care delivered by WeChat in discharged patients with AS, but they educated patients only through group chatting.…”
Section: Introductionmentioning
confidence: 99%
“…The education modules and text messages on the WCPRP public account were developed to provide simple, easy-to-understand health information, which was a viable way to connect medical staff and victims to facilitate health instruction delivery and resource sharing [9]. One previous study reported a successful outcome based on intervention for patients with type 2 diabetes via WeChat [10], and similar results were also found in a WeChat-based life review program for cancer patients [11].…”
Section: Discussionmentioning
confidence: 85%
“…Moreover, Zhang et al revealed that individualised health education through WeChat can play a central role in health education efforts in China because WeChat is well-integrated into society [18]. In recent years, some studies have found that interventions delivered by WeChat can improve health behaviors and health outcomes in patients with other chronic diseases [19][20][21][22]. Hu et al explored the transitional care delivered by WeChat in discharged patients with AS, but they educated patients only through group chatting [23].…”
Section: Introductionmentioning
confidence: 99%